The Role of School Principals in Promoting Inclusive Education - Anggi Rivana; Chai Pao; Roya Zahir; Misransyah Misransyah (International Journal of Educational Narratives, 2024)
Inclusive education has become a global priority in educational reform, aiming to provide all students, regardless of their abilities or disabilities, with equal opportunities to succeed. School principals play a vital role in fostering an inclusive environment, as they are responsible for leading the implementation of inclusive practices and promoting a culture of acceptance within the school community. However, there is a gap in understanding the specific roles and strategies school principals use to support inclusive education. This study aims to explore the role of school principals in promoting inclusive education, focusing on the strategies they employ, challenges they face, and the impact of their leadership on creating inclusive school environments. The study employed a qualitative research design, using in-depth interviews with 15 school principals across diverse educational settings. Data was analyzed thematically to identify key patterns in the principals’ approaches to inclusion, including leadership styles, professional development, and collaboration with teachers and parents. The findings indicate that school principals play a crucial role in fostering inclusive education by promoting inclusive policies, ensuring adequate resource allocation, and supporting professional development for teachers. However, challenges such as limited resources, resistance to change, and a lack of training were also identified. The study concludes that effective leadership by school principals is essential for the successful implementation of inclusive education. To overcome existing challenges, further professional development and a stronger emphasis on collaboration among educators and stakeholders are recommended.